Predicting consultants' teaching commitment to residency training program in Obstetrics and Gynecology private hospital setting. - David-Ruaro, Marilyn D.
Residency training may be viewed as the last step in the high-stakes education of licensed physicians who will practice as specialists in the field of obstetrics and gynecology (OBGYN) providing valuable correlation between theory and experience in the care of actual patients. In the Philippines, the Philippine Obstetrical and Gynecological Society (POGS) gives accreditation to training programs and later certifies its graduates to practice as OBGYN specialists. The influence of consultants' participation, or lack thereof, on the residents' learning process and on the effectiveness of hospital training programs has been demonstrated by many local studies. Private hospitals have added residency training to their hospital services and rely on their doctors who provide OBGYN services as private practitioners, and some as stockholders, to also function as teachers. There are now ninety four (94) hospitals with accredited OB-GYN training programs, fifty-two percent (52%) of these are in private hospitals. This survey used a self-administered questionnaire completed by eighty one respondents among 126 OB-GYN consultants at the Manila Doctors' Hospital (MDH), a tertiary private medical center in Manila, Philippines. Findings reveal that consultants were predominantly female with age range of 37 to 78 years, all certified in OBGYN practice, majority being subspecialists, all with high level of affective commitment towards teaching residents. By correlation and regression analysis, it was determined that in an institution primarily involved in delivery of private health care, being an active consultant and having a clinic in the hospital increased teaching commitment. The work-related factors predicting teaching commitment were: including consultants in curriculum preparation and in the schedule of structured learning activities, a reward system by the hospital recognizing teachers' performance, an official appointment or designation as faculty, a system of promotions to a more senior level, regular hospital-sponsored workshops on teaching, and an evaluation system of consultants' teaching performance. The study revealed strategies to increase teaching commitment of hospital consultants, enhance the lifelong learning opportunities of young doctors training to be specialists, contribute to effectiveness of the residency training programs, and eventually improve the quality of patient care. The results may be of interest to specialty training programs other than OBGYN, and all training hospitals interested to increase their consultants' teaching commitment